A Study of Disaster Management System with View of Manet Application - Kumar, Deepak; Srivastava, Ashutosh (JOURNAL OF ADVANCES IN PHYSICS, 2014)
In the modern era, Disaster Management has become an important field of study. With the advent of telecommunication system and their possible integration with the existing disaster management system, it is possible to minimize the after effects of disaster. In this paper we present a study of available and possible disaster management system based on wireless mobile telecommunication. In order to use such a system in the actual world security requirements such as availability, accountability, integrity and confidentiality must be ensured by the disaster management system.